Kajian Sosial Ekonomi SID Pantai Calang dan Pantai Krueng Sabee, Kota Aceh Jaya - Sumarna Hasan (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2011)
Town Calang besides area settlement location also as Calang municipal administration center with various activity of economics society. Around this area there are also fishery activity and fishpond as Coastal area fisherman society living of Calang. Effect of existence of Tsunami and earthquake have resulted changing coastal morphology where so that have resulted the resignment of coastline as for ± 100-200 m. Besides have eliminated coastal area, Tsunami have also eliminated some of joint streets pass by quickly Banda Aceh-Meulaboh which have location around this coast. Coastal protection of Calang and Krueng Sabee desides conducted with coastal building development, is also planned by coastal protection brand involved. Coastal protection involved represent bekt green with Coconut crop cultivation and Mangrove. Coastal Protection made in which suited for applied at this study location is breakwater building. Result of calculation from economic analysis, this development within 25 years at interest rate 24% estimated to have NPV equal to 1.018.582.359,72 net B/C 1,131 and IRR is 26,89%.